New use for an old reagent: Cell cycle analysis of DNA content using flow cytometry in formamide treated cells. Issue 5 (11th February 2016) - Carbonari, Maurizio
Abstract: Formamide has long been one of the most widely used reagents in the study of nucleic acids. However, the use of formamide for treating cells to be analyzed by flow cytometry is a recent development and is restricted to measuring telomere lengths by flow‐FISH. In this field, we have published several papers in order to observe the effects of formamide treatment on cells at room temperature. We therefore discovered that, with suitable modifications, a short and simple incubation in this ionizing solvent facilitates cell cycle analysis by flow cytometry, equivalent or superior to that obtained with treatments in alcohol, acetone or detergent in hypotonic solution. Even using a bulky and problematic stain (low quantum efficiency and G‐C base preference), such as 7‐aminoactinomycin D (7‐AAD) which, on the other hand, has the advantage of being excited at 488 nm and does not bind to the RNA, it is possible to obtain excellent coefficients of variation and (G2–M) mode/(G0–G1) mode ratios. These parameters, especially if stained cells are washed before acquisition, arrive at optimal values. It is noteworthy that the ability to wash the cells stained for DNA content analysis without affecting the stoichiometry of the staining has not been described elsewhere in the literature. With formamide treatment the doublets are practically absent, sample recovery is efficient, as well as the preservation of physical parameters, and the stained cells can be stored for at least 10 days at room temperature before acquisition. © 2016 International Society for Advancement of Cytometry